A seawater sea sand regenerated micro powder high-ductility geopolymer material, a preparation method thereof and application thereof

CN122958082APending Publication Date: 2026-10-23ZHEJIANG YIQING ENVIRONMENTAL PROTECTION ENG CO LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611352552.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-02
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

然而,现有研究尚未给出将多种再生微粉、海水、海砂、超高分子量聚乙烯纤维与无水固体碱激发剂等协同使用,制备兼具高延性和良好工作性的地质聚合物材料的方案

Benefits of technology

本发明通过再生混凝土粉、再生净浆粉和再生砖粉的多元复配,利用三种再生微粉在化学组成与反应活性上的天然互补性,即再生净浆粉的富钙组分促进地质聚合反应程度,再生砖粉的富硅铝组分补充活性前驱体,再生混凝土粉提供多相颗粒骨架,三者协同提高了基体密实度与纤维-基体界面粘结性能,解决了传统单一再生微粉活性偏低、反应程度不足的问题,同时大量消纳建筑垃圾,实现废弃资源的高附加值利用。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122958082A_ABST
    Figure CN122958082A_ABST
Patent Text Reader

Abstract

The application discloses a seawater-sea sand recycled micro-powder high-ductility geopolymer material, a preparation method and application thereof. The application solves the problems of low activity and insufficient reaction degree of traditional single recycled micro-powder by multi-element compounding of recycled concrete powder, recycled net paste powder and recycled brick powder, and by using the natural complementarity of the three kinds of recycled micro-powder in chemical composition and reaction activity. Meanwhile, a large amount of construction waste is absorbed, and high-value utilization of waste resources is realized. Seawater is directly used as the mixing medium, and sea sand is directly used as the fine aggregate. Ultra-high molecular weight polyethylene fibers are used as the toughening material. The nucleation effect of nano calcium carbonate is used to refine the matrix pore structure and enhance the frictional bonding of the fiber-matrix interface. The thickening and water-retention effect of cellulose ether is used to compensate for the high water absorption of the recycled micro-powder and ensure uniform dispersion of the fibers. The material has excellent high-ductility, good workability and long-term durability, and can meet the needs of different engineering scenes, and has a wide engineering application range.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a highly ductile geopolymer material made from recycled seawater sand, its preparation method, and its application, belonging to the field of building materials. Background Technology

[0002] With the large-scale generation of construction waste, recycled micropowders such as recycled concrete powder, recycled cement paste powder, and recycled brick powder are rich in silica, aluminum, and calcium components, and have the potential to serve as precursors for geopolymers. However, when used alone, their activity is low, the degree of geopolymerization is insufficient, and the matrix is ​​significantly brittle, making them difficult to utilize directly. Existing high-ductility geopolymers mostly use raw materials such as fly ash and slag with fresh water and river sand, and are toughened with polyvinyl alcohol fibers. However, polyvinyl alcohol fibers have insufficient alkali resistance. Although ultra-high molecular weight polyethylene fibers have better alkali resistance and suitable interfacial bonding, they are difficult to disperse uniformly in the porous and highly absorbent system of recycled micropowders, resulting in weak interfacial bonding and difficulty in obtaining stable high ductility. In island and near-shore engineering projects, freshwater and river sand resources are scarce. Directly utilizing seawater and sea sand can significantly reduce costs, and the fiber-reinforced system without steel reinforcement can avoid the risk of chloride ion corrosion. Appropriate amounts of chloride salts may also promote the early dissolution of siliceous aluminosilicate raw materials, but excessive salt ions can affect product stability. Meanwhile, liquid alkali activators are inconvenient to transport; using anhydrous sodium silicate and solid sodium hydroxide dissolved in seawater for activation can improve construction convenience. However, current research has not yet presented a scheme for the synergistic use of various recycled micropowders, seawater, sea sand, ultra-high molecular weight polyethylene fibers, and anhydrous solid alkali activators to prepare geopolymer materials that combine high ductility and good workability. Summary of the Invention

[0003] Purpose of the invention: The purpose of this invention is to provide a seawater sand recycled micronized geopolymer material with high ductility and good workability, its preparation method and application.

[0004] The seawater and sea sand recycled micropowder high-ductility geopolymer material of the present invention comprises the following components by weight: recycled micropowder: 3-5 parts; seawater: 0.1-2 parts; sea sand: 0.1-5 parts; anhydrous sodium silicate: 0.1-1 parts; sodium hydroxide: 0.1-1 parts; PE fiber: 0.05-0.5 parts; nano calcium carbonate: 0.01-0.1 parts; cellulose ether: 0.01-0.1 parts.

[0005] Furthermore, the recycled micro powder includes recycled concrete powder, recycled cement paste powder, and recycled brick powder, with 1 part of recycled concrete powder, 1-2 parts of recycled cement paste powder, and 1-2 parts of recycled brick powder.

[0006] Further, the functional material comprises the following components: recycled micro powder: 3-5 parts; seawater: 0.5-2 parts; sea sand: 1-5 parts; anhydrous sodium silicate: 0.3-1 parts; sodium hydroxide: 0.3-1 parts; PE fiber: 0.1-0.5 parts; nano calcium carbonate: 0.03-0.1 parts; cellulose ether: 0.03-0.1 parts; wherein recycled concrete powder is 1 part; recycled cement paste powder is 1-2 parts; and recycled brick powder is 1-2 parts.

[0007] Further, the functional material comprises the following components: recycled micro powder: 3 parts; seawater: 0.5 parts; sea sand: 1 part; anhydrous sodium silicate: 0.3 parts; sodium hydroxide: 0.3 parts; PE fiber: 0.1 parts; nano calcium carbonate: 0.03 parts; cellulose ether: 0.03 parts; wherein recycled concrete powder is 1 part; recycled cement paste powder is 1 part; and recycled brick powder is 1 part.

[0008] Further, the functional material comprises the following components: recycled micro powder: 4 parts; seawater: 1 part; sea sand: 3 parts; anhydrous sodium silicate: 0.5 parts; sodium hydroxide: 0.5 parts; PE fiber: 0.2 parts; nano calcium carbonate: 0.05 parts; cellulose ether: 0.05 parts; wherein recycled concrete powder is 1 part; recycled cement paste powder is 1.5 parts; and recycled brick powder is 1.5 parts.

[0009] Further, the functional material comprises the following components: recycled micro powder: 5 parts; seawater: 1.5 parts; sea sand: 5 parts; anhydrous sodium silicate: 0.8 parts; sodium hydroxide: 0.8 parts; PE fiber: 0.4 parts; nano calcium carbonate: 0.08 parts; cellulose ether: 0.08 parts; wherein recycled concrete powder is 1 part; recycled cement paste powder is 2 parts; and recycled brick powder is 2 parts.

[0010] Furthermore, the functional material comprises the following components: recycled micro powder: 5 parts; seawater: 2 parts; sea sand: 5 parts; anhydrous sodium silicate: 1 part; sodium hydroxide: 1 part; PE fiber: 0.5 parts; nano calcium carbonate: 0.1 parts; cellulose ether: 0.1 parts; wherein recycled concrete powder is 1 part; recycled cement paste powder is 2 parts; and recycled brick powder is 2 parts.

[0011] Furthermore, the recycled concrete powder is a fine powder obtained by grinding waste concrete after crushing and separation, with a particle size ≤75μm.

[0012] Furthermore, the recycled cement paste powder is a fine powder that is separately ground from the hardened cement paste in waste concrete, with a particle size ≤75μm.

[0013] Furthermore, the recycled brick powder is a fine powder obtained by crushing and grinding waste sintered bricks, with a particle size ≤75μm.

[0014] Furthermore, the seawater is natural seawater with a chloride ion concentration ≥10g / L.

[0015] Furthermore, the sea sand is natural sea sand with a particle size of 0.15-5 mm. The chloride ion concentration is ≥10 g / L.

[0016] Furthermore, the anhydrous sodium silicate is a powdered solid with a modulus of 1.0-2.5.

[0017] Furthermore, the sodium hydroxide is an industrial-grade flake or granular solid with a purity ≥95%.

[0018] Furthermore, the PE fiber is ultra-high molecular weight polyethylene fiber, with a length of 6-24 mm and a diameter of 15-50 μm. Its modulus is 91-140 N / tex.

[0019] Furthermore, the average particle size of the nano-calcium carbonate is 20-200 nm.

[0020] Furthermore, the cellulose ether includes one or more of methylcellulose ether, hydroxyethylcellulose ether, hydroxypropyl methylcellulose ether, carboxymethylcellulose ether, and ethyl hydroxyethylcellulose ether.

[0021] The present invention discloses a method for preparing a highly ductile geopolymer material from recycled seawater sand powder, characterized by comprising the following steps: (1) Mix the recycled micro powder, anhydrous sodium silicate, sodium hydroxide, cellulose ether and sea sand, stir evenly, and prepare a premixed compound; (2) Disperse nano-calcium carbonate in seawater in advance, and prepare nano-calcium carbonate suspension by ultrasonic or high-speed stirring. Then add seawater containing nano-calcium carbonate to the premix and stir. After mixing evenly, add PE fiber in batches while stirring until the fiber is evenly distributed to obtain the final mixture. (3) The final mixture is then placed into a mold for curing.

[0022] Furthermore, the recycled micro powder includes recycled concrete powder, recycled cement paste powder, and recycled brick powder.

[0023] Furthermore, the PE fibers are added in 3-5 portions.

[0024] The present invention relates to the application of a highly ductile geopolymer material made from recycled seawater sand powder in the preparation of building materials.

[0025] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: This invention utilizes a multi-component compound of recycled concrete powder, recycled cement paste powder, and recycled brick powder. It leverages the natural complementarity of these three recycled powders in terms of chemical composition and reactivity. Specifically, the calcium-rich component of the recycled cement paste powder promotes the degree of geopolymerization reaction, the silicon-aluminum-rich component of the recycled brick powder supplements the active precursor, and the recycled concrete powder provides a multiphase particle skeleton. The three components synergistically improve the matrix density and fiber-matrix interface bonding performance, solving the problems of low activity and insufficient reactivity of traditional single recycled powders. At the same time, it can absorb a large amount of construction waste and achieve high-value-added utilization of waste resources.

[0026] (2) Based on this, seawater is used directly as the mixing medium and sea sand as fine aggregate. Seawater is used to activate anhydrous sodium silicate and sodium hydroxide in situ. Chloride ions in seawater promote the early dissolution and geological polymerization reaction rate of siliceous aluminum raw materials, replacing traditional fresh water and natural river sand. This significantly reduces the material transportation cost and environmental load of island and coastal engineering construction. In addition, in the non-steel-reinforced system with non-metallic fiber toughening, the corrosion risk of chloride ions and sulfate ions is effectively avoided.

[0027] (3) Further use of ultra-high molecular weight polyethylene fiber as toughening material, refine the matrix pore structure and enhance the fiber-matrix interface friction bonding through the nucleation effect of nano-calcium carbonate, compensate the high water absorption of recycled micro powder through the thickening and water retention effect of cellulose ether and ensure uniform fiber dispersion, optimize the fiber-matrix interface bonding characteristics, avoid insufficient fiber pull-out energy consumption caused by a single weak interface or excessive bonding, significantly improve the tensile strain hardening behavior and multi-crack characteristics of the material, solve the problem of high brittleness and insufficient ductility of traditional recycled micro powder geopolymer, and greatly improve the deformation capacity and seismic performance of the material.

[0028] (4) The geopolymer material of the present invention has excellent high ductility, good working performance and long-term durability, meets the needs of different engineering scenarios and has a wide range of engineering applications. Attached Figure Description

[0029] Figure 1 The compressive strength results are for the materials prepared as comparative examples of this invention.

[0030] Figure 2 The results of preparing compressive strength materials according to embodiments of the present invention.

[0031] Figure 3 The tensile strain results of the materials prepared as comparative examples of the present invention are shown.

[0032] Figure 4 The tensile strain results of the materials prepared in the embodiments of the present invention are shown. Detailed Implementation

[0033] The technical solution of the present invention will be further described below with reference to the accompanying drawings.

[0034] The preparation process of a highly ductile geopolymer material made from recycled seawater sand powder according to the present invention is as follows: Take 1 part of recycled concrete powder, 1-2 parts of recycled cement paste powder, 1-2 parts of recycled brick powder, 0.1-1 part of anhydrous sodium silicate, 0.1-1 part of sodium hydroxide, 0.01-0.1 part of cellulose ether, and 0.1-5 parts of sea sand, mix them evenly, and obtain a premixed compound.

[0035] Disperse 0.01-0.1 parts of nano-calcium carbonate in 0.1-2 parts of seawater, and prepare a nano-calcium carbonate suspension by ultrasonic or high-speed stirring. Then add the seawater containing nano-calcium carbonate to the premix and stir. After mixing evenly, add 0.05-0.5 parts of PE fiber in batches while stirring, and stir until the fiber is evenly distributed to obtain the final mixture. The final mixture obtained is then poured into a mold, thoroughly vibrated, and the entire mold is covered with plastic wrap. Curing methods include sealed room temperature curing or humid heat curing, with a curing temperature of 20-80℃, a relative humidity of 70-98%, and a curing period of 1-28 days. Finally, a highly ductile geopolymer material made from recycled seawater sand powder is obtained.

[0036] Raw material requirements: Recycled concrete powder is a fine powder obtained from waste concrete through crushing, separation, and grinding, with a particle size ≤75μm. The "separation" process specifically involves: coarse crushing of waste concrete blocks using a jaw crusher, medium crushing using an impact crusher or cone crusher, followed by screening and grading using a vibrating screen. Aggregates with a particle size greater than 2.36 mm (mainly natural crushed stone or pebbles) are separated out, while sand powder with a particle size less than 2.36 mm (including recycled sand, unhydrated cement particles, and some hardened cement paste debris) is collected as grinding raw material. The original strength grade of the waste concrete is ≥C20. The recycled concrete powder is used in a completely dry state. Pre-treatment before use involves placing the recycled concrete powder in a drying oven at 100-110℃ for 24 hours, with a mass change <0.1%. In this example, the recycled concrete powder was prepared in-house after obtaining waste concrete. The waste concrete comes from waste concrete blocks generated during urban infrastructure construction, old city renovation, demolition of existing buildings, and maintenance and upgrading of roads and bridges, which are recycled by Zhejiang Yiqing Environmental Protection Engineering Co., Ltd. The waste mainly comes from the demolition waste of concrete components such as frame structures, shear wall structures, and roads and bridges.

[0037] Recycled slurry powder is a fine powder obtained by grinding waste slurry, with a particle size ≤75μm. The recycled slurry powder is used in a completely dry state. Pre-treatment before use involves placing the recycled slurry powder in a drying oven at 100-110℃ for 24 hours, with a mass change of <0.1%. In the examples, the recycled slurry powder was obtained from waste slurry with an original strength ≥20 MPa, prepared by the laboratory of civil engineering materials at Shaoxing University through in-house grinding.

[0038] Recycled brick powder is a fine powder obtained by crushing and grinding waste sintered bricks, with a particle size ≤75μm. The original strength grade of the waste sintered bricks is ≥MU5.0, and the impurity content is <0.1%. The recycled brick powder is used in a completely dry state. The pretreatment before use involves placing the recycled brick powder in a drying oven at 100-110℃ for 24 hours, with a mass change of <0.1%. In the example, the recycled brick powder was prepared by the company after obtaining waste sintered bricks. The waste sintered bricks are construction waste generated during urban renewal, existing building maintenance, and demolition processes recycled by Zhejiang Yiqing Environmental Protection Engineering Co., Ltd., mainly from the demolition waste of brick-concrete structures.

[0039] The seawater used was either natural seawater or artificially prepared seawater, with a chloride ion concentration ≥10g / L. In the examples, the seawater was sourced from the natural seawater off the coast of Qingdao.

[0040] The sea sand is either natural sea sand or desalinated sea sand, with a particle size of 0.15-5mm, a mud content of <1.0%, and a chloride ion content of ≤0.06%. The sea sand is dried or sun-dried before use to ensure it is in a dry state. In this example, the sea sand is sourced from natural sea sand found in the coastal waters of Qingdao.

[0041] Anhydrous sodium silicate is a powdered solid with a modulus of 1.0-2.5 and a purity of ≥95%.

[0042] Sodium hydroxide is an industrial-grade flaky or granular solid with a purity ≥95%. PE fiber is ultra-high molecular weight polyethylene fiber with an elastic modulus of 91-140 N / tex, a length of 6-24 mm, and a diameter of 15-50 μm. In the examples, the PE fiber is sourced from Beijing Quantum World New Materials Technology Co., Ltd.

[0043] The average particle size of nano-calcium carbonate is 20-200 nm, and the purity is ≥95%.

[0044] The cellulose ether is hydroxypropyl methylcellulose ether.

[0045] Example 1

[0046] One part of recycled concrete powder, one part of recycled cement paste powder, one part of recycled brick powder, 0.5 parts of anhydrous sodium silicate, 0.5 parts of sodium hydroxide, 0.03 parts of cellulose ether, and 1.0 part of sea sand were measured and mixed evenly to obtain a premix. 0.03 parts of nano-calcium carbonate were pre-dispersed in 0.5 parts of seawater and treated using a probe-type ultrasonic dispersion device. The ultrasonic working frequency was set to 28 kHz, the ultrasonic power to 750 W (adjustable amplitude 60%), and intermittent ultrasonic treatment was performed using pulse mode (5 s on, 5 s off). The total ultrasonic time was 30–40 min. During the treatment, the suspension container was placed in an ice-water bath to maintain the system temperature at 20–25 °C. After this dispersion, the nano-calcium carbonate agglomerates were effectively deagglomerated (the median particle size could be reduced from micrometers to below 158 nm, and some could reach below 100 nm), resulting in a stable nano-calcium carbonate suspension. Next, seawater containing nano-calcium carbonate is added to the premix and stirred. After mixing evenly, 0.2 parts of PE fiber are added in 5 batches while stirring until the fiber is evenly distributed, thus obtaining the final mixture.

[0047] Among them, recycled concrete powder is a fine powder obtained by crushing, separating, and grinding waste concrete, with a particle size ≤75μm. Recycled cement paste powder is a fine powder obtained by grinding hardened cement paste separated from waste concrete, with a particle size ≤75μm. Recycled brick powder is a fine powder obtained by crushing and grinding waste sintered bricks, with a particle size ≤75μm. The original strength grade of the waste concrete is C25, and the original strength grade of the waste sintered bricks is MU5.0. All three recycled powders are in a completely dry state and are dried in a drying oven at 105℃ for 24 hours before use, with a mass change of <0.1%. Anhydrous sodium silicate is a powdered solid with a modulus of 2.0 and a purity ≥95%. Sodium hydroxide is an industrial-grade flaky solid with a purity ≥95%. Seawater is natural seawater with a chloride ion concentration ≥10g / L. Sea sand is natural sea sand with a particle size of 0.15-5mm, and is dried before use. The PE fiber is ultra-high molecular weight polyethylene fiber with an elastic modulus of 91-140 N / tex, a length range of 12-18 mm, and a diameter of 15-50 μm. The nano-calcium carbonate has an average particle size of 20-200 nm and a purity of ≥95%. The cellulose ether is hydroxypropyl methylcellulose ether.

[0048] The final mixture obtained is then poured into the mold, thoroughly vibrated, and then the entire mold is covered with plastic wrap. The curing method is sealed and room temperature curing, with a curing temperature of 20±2℃, a relative humidity of 70-95%, and a curing period of 28 days.

[0049] Example 2

[0050] One part of recycled concrete powder, 1.5 parts of recycled cement paste powder, 1.5 parts of recycled brick powder, 0.5 parts of anhydrous sodium silicate, 0.5 parts of sodium hydroxide, 0.05 parts of cellulose ether, and 2.0 parts of sea sand were measured and mixed evenly to obtain a premix. 0.05 parts of nano-calcium carbonate were pre-dispersed in 1.0 part of seawater and treated using a probe-type ultrasonic dispersion device. The ultrasonic working frequency was set to 28 kHz, the ultrasonic power to 750 W (adjustable amplitude 60%), and intermittent ultrasonic treatment was performed using a pulse mode (5 s on, 5 s off). The total ultrasonic time was 30–40 min. During the treatment, the suspension container was placed in an ice-water bath to maintain the system temperature at 20–25 °C. After this dispersion, the nano-calcium carbonate agglomerates were effectively deagglomerated (the median particle size could be reduced from micrometers to below 158 nm, and some could reach below 100 nm), resulting in a stable nano-calcium carbonate suspension. Next, seawater containing nano-calcium carbonate is added to the premix and stirred until it is evenly mixed. Then, 0.3 parts of PE fiber are added in 5 batches while stirring until the fiber is evenly distributed, thus obtaining the final mixture.

[0051] The material conditions are the same as in Example 1.

[0052] The final mixture obtained is then poured into the mold, thoroughly vibrated, and the entire mold is covered with plastic wrap. The curing method is sealed and room temperature curing, with a curing temperature of 20±2℃ and a curing period of 28 days.

[0053] Example 3

[0054] One part of recycled concrete powder, two parts of recycled cement paste powder, two parts of recycled brick powder, 0.8 parts of anhydrous sodium silicate, 0.8 parts of sodium hydroxide, 0.08 parts of cellulose ether, and 5.0 parts of sea sand were measured and mixed evenly to obtain a premix. 0.08 parts of nano-calcium carbonate were pre-dispersed in 1.5 parts of seawater and treated using a probe-type ultrasonic dispersion device. The ultrasonic working frequency was set to 28 kHz, the ultrasonic power to 750 W (adjustable amplitude 60%), and intermittent ultrasonic treatment was performed using a pulse mode (5 s on, 5 s off). The total ultrasonic time was 30–40 min. During the treatment, the suspension container was placed in an ice-water bath to maintain the system temperature at 20–25 °C. After this dispersion, the nano-calcium carbonate agglomerates were effectively deagglomerated (the median particle size could be reduced from micrometers to below 158 nm, and some could reach below 100 nm), resulting in a stable nano-calcium carbonate suspension. Next, seawater containing nano-calcium carbonate is added to the premix and stirred until it is evenly mixed. Then, 0.3 parts of PE fiber are added in 5 batches while stirring until the fiber is evenly distributed, thus obtaining the final mixture.

[0055] The material conditions are the same as in Example 1.

[0056] The final mixture obtained is then poured into the mold, thoroughly vibrated, and the entire mold is covered with plastic wrap. The curing method is sealed and room temperature curing, with a curing temperature of 20±2℃ and a curing period of 28 days.

[0057] Example 4

[0058] One part of recycled concrete powder, two parts of recycled cement paste powder, two parts of recycled brick powder, one part of anhydrous sodium silicate, one part of sodium hydroxide, one part of cellulose ether, and five parts of sea sand were measured and mixed evenly to obtain a premix. One part of nano-calcium carbonate was pre-dispersed in one part of seawater and treated using a probe-type ultrasonic dispersion device. The ultrasonic working frequency was set to 28 kHz, the ultrasonic power to 750 W (adjustable amplitude 60%), and intermittent ultrasonic treatment was performed using a pulse mode (5 s on, 5 s off). The total ultrasonic time was 30–40 min. During the treatment, the suspension container was placed in an ice-water bath to maintain the system temperature at 20–25 °C. After this dispersion, the nano-calcium carbonate agglomerates were effectively deagglomerated (the median particle size could be reduced from micrometers to below 158 nm, and some could reach below 100 nm), resulting in a stable nano-calcium carbonate suspension. Next, seawater containing nano-calcium carbonate is added to the premix and stirred. After mixing evenly, 0.4 parts of PE fiber are added in 5 batches while stirring until the fiber is evenly distributed, thus obtaining the final mixture.

[0059] The material conditions are the same as in Example 1.

[0060] The final mixture obtained is then poured into the mold, thoroughly vibrated, and then the entire mold is covered with plastic wrap. The curing method is sealed and room temperature curing, with a curing temperature of 20±2 ℃ and a curing period of 28 days.

[0061] Compare with Example 1 Three parts of recycled concrete powder, 0.5 parts of anhydrous sodium silicate, 0.5 parts of sodium hydroxide, 0.05 parts of cellulose ether, and 2.0 parts of sea sand were measured and mixed evenly to obtain a premix. 0.05 parts of nano-calcium carbonate were pre-dispersed in 1.0 part of seawater and treated using a probe-type ultrasonic dispersion device. The ultrasonic working frequency was set to 28 kHz, the ultrasonic power to 750 W (adjustable amplitude 60%), and intermittent ultrasonic treatment was performed using a pulse mode (5 s on, 5 s off). The total ultrasonic time was 30–40 min. During the treatment, the suspension container was placed in an ice-water bath to maintain the system temperature at 20–25 °C. After this dispersion, the nano-calcium carbonate agglomerates were effectively deagglomerated (the median particle size could be reduced from micrometers to below 158 nm, and some could reach below 100 nm), resulting in a stable nano-calcium carbonate suspension. Next, seawater containing nano-calcium carbonate is added to the premix and stirred. After mixing evenly, 0.2 parts of PE fiber are added in 5 batches while stirring until the fiber is evenly distributed, thus obtaining the final mixture.

[0062] Among them, recycled concrete powder is a fine powder obtained by crushing, separating, and grinding waste concrete, with a particle size ≤75 μm. Anhydrous sodium silicate is a powdered solid with a modulus of 2.0 and a purity ≥95%. Sodium hydroxide is an industrial-grade flaky solid with a purity ≥95%. Seawater is natural seawater with a chloride ion concentration ≥10 g / L. Sea sand is natural sea sand with a particle size of 0.15-5 mm, which is dried before use. PE fiber is ultra-high molecular weight polyethylene fiber with an elastic modulus of 91-140 N / tex and a length range of 12-18 mm. Nano-calcium carbonate has an average particle size of 20-200 nm and a purity ≥95%. Cellulose ether is hydroxypropyl methylcellulose ether.

[0063] The final mixture obtained is then poured into the mold, thoroughly vibrated, and the entire mold is covered with plastic wrap. The curing method is sealed and room temperature curing, with a curing temperature of 20±2℃ and a curing period of 28 days.

[0064] Compare with Example 2 1.5 parts of recycled concrete powder, 1.5 parts of recycled brick powder, 0.5 parts of anhydrous sodium silicate, 0.5 parts of sodium hydroxide, 0.05 parts of cellulose ether, and 2.0 parts of sea sand were measured and mixed evenly to obtain a premix. 0.05 parts of nano-calcium carbonate were pre-dispersed in 1.0 part of seawater and treated using a probe-type ultrasonic dispersion device. The ultrasonic working frequency was set to 28 kHz, the ultrasonic power was 750 W (adjustable amplitude 60%), and intermittent ultrasonic treatment was performed using pulse mode (5 s on, 5 s off) for a total ultrasonic time of 30–40 min. During the treatment, the suspension container was placed in an ice-water bath to maintain the system temperature at 20–25°C. After this dispersion, the nano-calcium carbonate agglomerates were effectively deagglomerated (the median particle size could be reduced from micrometers to below 158 nm, and some could reach below 100 nm), resulting in a stable nano-calcium carbonate suspension. Next, seawater containing nano-calcium carbonate is added to the premix and stirred. After mixing evenly, 0.2 parts of PE fiber are added in 5 batches while stirring until the fiber is evenly distributed, thus obtaining the final mixture.

[0065] Among them, recycled brick powder is a fine powder obtained by crushing and grinding waste sintered bricks, with a particle size ≤75 μm. Recycled concrete powder, anhydrous sodium silicate, sodium hydroxide, nano calcium carbonate, cellulose ether, sea sand, seawater, and PE fiber are the same as in control example 1.

[0066] The final mixture obtained is then poured into the mold, thoroughly vibrated, and the entire mold is covered with plastic wrap. The curing method is sealed and room temperature curing, with a curing temperature of 20±2℃ and a curing period of 28 days.

[0067] Design objective: The binary blend of recycled concrete powder and recycled brick powder (a common combination in existing technologies) relies solely on calcium-rich and silicon-aluminum-rich components, lacking the interface optimization effect of pure cement hydration products from recycled cement paste powder.

[0068] Compare with Example 3 1.5 parts of recycled concrete powder, 1.5 parts of recycled cement paste powder, 0.5 parts of anhydrous sodium silicate, 0.5 parts of sodium hydroxide, 0.05 parts of cellulose ether, and 2.0 parts of sea sand were measured and mixed evenly to obtain a premix. 0.05 parts of nano-calcium carbonate were pre-dispersed in 1.0 part of seawater and treated using a probe-type ultrasonic dispersion device. The ultrasonic working frequency was set to 28 kHz, the ultrasonic power was 750 W (adjustable amplitude 60%), and intermittent ultrasonic treatment was performed using pulse mode (5 s on, 5 s off) for a total ultrasonic time of 30–40 min. During the treatment, the suspension container was placed in an ice-water bath to maintain the system temperature at 20–25 °C. After this dispersion, the nano-calcium carbonate agglomerates were effectively deagglomerated (the median particle size could be reduced from micrometers to below 158 nm, and some could reach below 100 nm), resulting in a stable nano-calcium carbonate suspension. Next, seawater containing nano-calcium carbonate is added to the premix and stirred. After mixing evenly, 0.2 parts of PE fiber are added in 5 batches while stirring until the fiber is evenly distributed, thus obtaining the final mixture.

[0069] Among them, the recycled cement paste powder is a fine powder obtained by grinding hardened cement paste separated from waste concrete, with a particle size ≤75 μm. The recycled concrete powder, anhydrous sodium silicate, sodium hydroxide, nano calcium carbonate, cellulose ether, sea sand, seawater, and PE fiber are the same as those in control example 1.

[0070] The final mixture obtained is then poured into the mold, thoroughly vibrated, and the entire mold is covered with plastic wrap. The curing method is sealed and room temperature curing, with a curing temperature of 20±2℃ and a curing period of 28 days.

[0071] Design objective: The binary blend of recycled concrete powder and recycled cement paste powder lacks the silicon-aluminum-rich component of recycled brick powder, resulting in incomplete gradient activity complementarity.

[0072] Compare with Example 4 One part of recycled concrete powder, one part of recycled cement paste powder, one part of recycled brick powder, 0.5 parts of anhydrous sodium silicate, 0.5 parts of sodium hydroxide, 0.05 parts of cellulose ether, and 2.0 parts of river sand were measured and mixed evenly to obtain a premixed compound. 0.05 parts of nano-calcium carbonate were pre-dispersed in 1.0 part of fresh water and treated using a probe-type ultrasonic dispersion device. The ultrasonic working frequency was set to 28 kHz, the ultrasonic power to 750 W (adjustable amplitude 60%), and intermittent ultrasonic treatment was performed using pulse mode (5 s on, 5 s off). The total ultrasonic time was 30–40 min. During the treatment, the suspension container was placed in an ice-water bath to maintain the system temperature at 20–25 °C. After this dispersion, the nano-calcium carbonate agglomerates were effectively deagglomerated (the median particle size could be reduced from micrometers to below 158 nm, and some could reach below 100 nm), resulting in a stable nano-calcium carbonate suspension. Next, add fresh water containing nano-calcium carbonate to the premix and stir. After mixing evenly, add 0.2 parts of PE fiber in 5 batches while stirring, stirring until the fiber is evenly distributed to obtain the final mixture.

[0073] The river sand used was natural river sand with a particle size of 0.15–5 mm, and was in a completely dry state. The river sand originated from natural river channels, riverbeds, or ancient riverbed sedimentary layers, obtained through river sand mining operations. It mainly consisted of natural siliceous sand particles formed by long-term river scouring, transportation, and deposition, with quartz as the primary mineral component, and also containing small amounts of feldspar, mica, and other rock fragments. The mined natural river sand was transported to a sand washing plant, where it was washed to remove harmful impurities such as mud, mica, light materials, and organic matter. It was then sieved and graded using a vibrating screen, selecting continuously graded river sand with a particle size of 0.15–5 mm as raw material. The sieved river sand was then placed in an oven and dried to constant weight at 105±5 °C to obtain completely dry river sand for later use. Ordinary tap water was used. Recycled concrete powder, recycled cement paste powder, recycled brick powder, anhydrous sodium silicate, sodium hydroxide, nano-calcium carbonate, cellulose ether, and PE fiber were all the same as in Control Examples 1 to 3.

[0074] The final mixture obtained is then poured into the mold, thoroughly vibrated, and the entire mold is covered with plastic wrap. The curing method is sealed and room temperature curing, with a curing temperature of 20±2℃ and a curing period of 28 days.

[0075] The comprehensive performance of the materials prepared in Comparative Examples 1-4 and Examples 1-4 was evaluated, and the results are shown in Table 1. Figures 1-4 As shown.

[0076] The specimen used was a standard dog bone specimen with an overall length of 330 mm, an effective gauge length of 80 mm, and a cross-sectional thickness of 13 mm. The ultimate tensile strain, ultimate tensile strength, and average crack width were routine performance tests, and the number of cracks was obtained by counting the cracks on the inner surface of the gauge section of the specimen after the tensile test.

[0077] Uniaxial tensile tests were performed using a universal testing machine with a displacement rate of 0.5 mm / min. Strain data were collected in real time using an extensometer installed in the gauge length, and the stress-strain curve was recorded until the specimen failed to obtain the ultimate tensile strength and ultimate tensile strain. At least three parallel specimens were retained for each set of specimens, and outliers deviating from the mean by more than 20% were removed before taking the average value.

[0078] The specimens were 40 mm × 40 mm × 40 mm cube specimens. The compressive strength was a routine performance test, calculated from the maximum load and the area of ​​compression at specimen failure.

[0079] Compressive strength tests were conducted using a universal testing machine. A uniform load was applied at a loading rate of 2.4 kN / s ± 0.2 kN / s until specimen failure, and the maximum failure load F (N) was recorded. After specimen failure, the failure mode was observed and recorded, and the compressive strength was calculated using the formula σ_c = F / A, where A is the area of ​​the specimen subjected to compression (1600 mm²). At least three parallel specimens were retained for each set of specimens, and the average value was taken after removing outliers deviating from the mean by more than 15%.

[0080] Table 1

[0081] A comparison of Comparative Example 1 and Example 2 shows that in the seawater-sand geopolymer system, replacing single recycled concrete powder with a ternary blend of recycled concrete powder, recycled cement paste powder, and recycled brick powder, along with the synergistic incorporation of nano-calcium carbonate and cellulose ether, significantly improves the mechanical properties and high ductility of the material. Compared to Comparative Example 1, which uses only single recycled concrete powder, Example 2 shows an increase in ultimate tensile strain from 3.2% to 8.53%, a 166.6% increase; ultimate tensile strength from 5.0 MPa to 8.89 MPa, a 77.8% increase; and compressive strength from 48.5 MPa to 98.7 MPa, a 103.5% increase, demonstrating a significant leap in overall performance.

[0082] Comparing Example 2 with Comparative Examples 2, 3, and 4, it can be seen that Example 2 effectively solves the problems of insufficient calcium-rich components due to the lack of recycled cement paste powder when the binary compound of recycled concrete powder and recycled brick powder is made under seawater and sea sand conditions, insufficient silicon-aluminum-rich components due to the lack of recycled brick powder when the binary compound of recycled concrete powder and recycled cement paste powder is made under seawater and sea sand conditions, and low reaction degree due to the lack of seawater promoting effect when the ternary recycled micro powder is made under freshwater river sand conditions. This invention utilizes seawater to in-situ activate anhydrous sodium silicate and sodium hydroxide, leveraging chloride ions in seawater to accelerate the early dissolution and geopolymerization reaction rate of siliceous aluminate raw materials. The synergistic complementarity between the calcium-rich component of recycled cementitious mortar powder and the silicon-aluminate-rich component of recycled brick powder enhances matrix density and fiber-matrix interfacial bonding properties. Simultaneously, the combined action of nano-calcium carbonate and cellulose ether refines the matrix pore structure, compensates for the high water absorption of recycled micropowder, and ensures uniform dispersion of PE fibers, further achieving a simultaneous increase in matrix density and fiber dispersion. This results in a significant increase in tensile strain, tensile strength, and compressive strength, constructing a multi-scale reinforcement system that combines seawater sand activation, multi-component recycled micropowder synergistic compounding, and synergistic optimization of nano-calcium carbonate and cellulose ether.

Claims

1. A highly ductile geopolymer material made from recycled seawater sand powder, characterized in that, By weight, it includes the following components: Regenerated micro powder: 3-5 parts; Seawater: 0.1-2 parts; Sea sand: 0.1-5 parts; Anhydrous sodium silicate: 0.1-1 part; Sodium hydroxide: 0.1-1 part; PE fiber: 0.05-0.5 parts; Nano-calcium carbonate: 0.01-0.1 parts; Cellulose ether: 0.01-0.1 parts.

2. The high-ductility geopolymer material made from recycled seawater sand powder according to claim 1, characterized in that, The recycled micro powder includes recycled concrete powder, recycled cement paste powder and recycled brick powder, wherein the recycled concrete powder is 1 part; the recycled cement paste powder is 1-2 parts; and the recycled brick powder is 1-2 parts.

3. The high-ductility geopolymer material made from recycled seawater sand powder according to claim 2, characterized in that, The functional material comprises the following components: Regenerated micro powder: 3-5 parts; Seawater: 0.5-2 parts; Sea sand: 1-5 parts; Anhydrous sodium silicate: 0.3-1 part; Sodium hydroxide 0.3-1 serving; PE fiber: 0.1-0.5 parts; Nano calcium carbonate: 0.03-0.1 parts; Cellulose ether: 0.03-0.1 parts; of which 1 part is recycled concrete powder; 1-2 parts is recycled cement paste powder; and 1-2 parts is recycled brick powder.

4. The high-ductility geopolymer material made from recycled seawater sand powder according to claim 2, characterized in that, The recycled concrete powder is a fine powder made by grinding waste concrete after crushing and separation, with a particle size ≤75μm.

5. The high-ductility geopolymer material made from recycled seawater sand powder according to claim 2, characterized in that, The recycled cement paste powder is a fine powder made by separately grinding hardened cement paste from waste concrete, with a particle size ≤75μm.

6. The high-ductility geopolymer material made from recycled seawater sand powder according to claim 2, characterized in that, The recycled brick powder is a fine powder made from crushed and ground waste sintered bricks, with a particle size ≤75μm.

7. The high-ductility geopolymer material made from recycled seawater sand powder according to claim 2, characterized in that, The PE fiber is ultra-high molecular weight polyethylene fiber, with a length of 6-24 mm, a diameter of 15-50 μm, and a modulus of 91-140 N / tex.

8. The method for preparing the high-ductility geopolymer material made from recycled seawater sand according to any one of claims 1 to 7, characterized in that, Includes the following steps: (1) Mix the recycled micro powder, anhydrous sodium silicate, sodium hydroxide, cellulose ether and sea sand, stir evenly, and prepare a premixed compound; (2) Disperse nano-calcium carbonate in seawater in advance, and prepare nano-calcium carbonate suspension by ultrasonic or high-speed stirring. Then add seawater containing nano-calcium carbonate to the premix and stir. After mixing evenly, add PE fiber in batches while stirring until the fiber is evenly distributed to obtain the final mixture. (3) The final mixture is then placed into a mold for curing.

9. The preparation method according to claim 8, characterized in that, The PE fiber is added in 3-5 portions.

10. The application of the seawater sand recycled micro powder high ductility geopolymer material according to any one of claims 1 to 7 in the preparation of building materials.